2015
DOI: 10.1021/acs.langmuir.5b00489
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Water and Butanol in Silicalite-1 Film Studied with in Situ Attenuated Total Reflectance–Fourier Transform Infrared Spectroscopy

Abstract: Biobutanol produced by, e.g., acetone-butanol-ethanol (ABE) fermentation is a promising alternative to petroleum-based chemicals as, e.g., solvent and fuel. Recovery of butanol from dilute fermentation broths by hydrophobic membranes and adsorbents has been identified as a promising route. In this work, the adsorption of water and butanol vapor in a silicalite-1 film was studied using in situ attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy to better understand the adsorption pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 58 publications
(112 reference statements)
6
56
3
Order By: Relevance
“…28 In the procedure, the contribution from OH stretching vibration from adsorbed n-butanol was subtracted from the total signal using single component adsorption spectra of butanol. The butanol/water adsorption selectivities (α BuOH/water described in eq 1 obtained from the spectra were 165 and 14, for the SCTPAF and SCTPAOH samples, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In the procedure, the contribution from OH stretching vibration from adsorbed n-butanol was subtracted from the total signal using single component adsorption spectra of butanol. The butanol/water adsorption selectivities (α BuOH/water described in eq 1 obtained from the spectra were 165 and 14, for the SCTPAF and SCTPAOH samples, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Band intensities have previously been calibrated against volumetric adsorption isotherms enabling the adsorbed concentrations to be extracted from infrared spectra. 28 Adsorption selectivity is determined as…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Recent research shows that the butanol/water adsorption selectivity of a MFI adsorbent may be further increased by decreasing the density of structural defects, in the form of silanol groups, present in the framework [25,26]. These defects are formed during conventional zeolite synthesis at high pH.…”
Section: Resultsmentioning
confidence: 99%
“…from model solutions and very little attention was given to recovery from real fermentation broths. Most studies have been performed on adsorption from liquid phase; however, recently, it was shown that high silica MFI zeolite showed very high butanol selectivity from vapor phase as reported by our group previously [25,26]. As zeolite MFI is a stable material and strightforward to synthesize in its hydrophobic (high Si/Al ratio) form at relatively low cost, it is one of the most studied materials for recovering butanol from dilute aqueous solutions.…”
Section: Introductionmentioning
confidence: 87%
“…Silicalite, a polymorph of silica with a structure analogous to the zeolites, is a compound with a very high SiO 2 /Al 2 O 3 ratio, a parameter which indicates the hydrophobicity level of the material's surface. Farzaneh et al (2015) demonstrated its suitability to separate butanol from the vapour obtained in an ABE fermentation gasstripping process (85:15 v H2O /v Bu-OH ), as silicalite-1 was butanol-selective with an adsorption selectivity of 107 at 35°C [228]. Silicalite-1, the pure silica analogue of the zeolite ZSM-5, has been stated as the most promising adsorbent for biobutanol recovery regarding its high adsorption capacity and selectivity, high stability and desorption ease by heating at 200°C [161].…”
Section: Adsorptionmentioning
confidence: 99%